Analysis of the decision-making styles of graduates of engineering courses - Pantoja, Hugo Glória; Gonçalves, Everton Jucelin Braz; Oliveira, Elizângela de Jesus (Brazilian Journal of Production Engineering, 2020)
Whether professionally or personally, decisions need to be made daily, decisions that directly interfere in the future of the individual or the organization. Decision-making is not always carried out rationally, just as it is not always taken suddenly. From this, it is of utmost importance to also know the decision-making styles of the professionals that are being developed in these institutions, considering that the styles are related to the personality and the context of each one. This article aims to identify the decision-making styles of final year students in Engineering courses and how these styles will interfere in the academic environment and in the job market. Through a questionnaire hosted on the SURVIO platform, 31 engineering students were interviewed in which it was possible to analyze through the questions the predominant decision-making style, being these: directive, analytical, conceptual and behavioral. It was possible to notice that the interviewees have a tendency towards analytical style, showing that the market tends to absorb more rational engineers and that engineering is a very wide area, with a variation of decision styles between courses.
Keywords: Decision; Decision making style; Engineering